Enhancing Budget Planning and Control for Sustainable Development Goals (SDGs): A Case Study of Yayasan Kebudayaan Rancage - Margaretha, Patricia; Soenaria, Syaiful Rahman (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
This study analyzes budget planning and control in a nonprofit organization. The primary objective is to explore how the budget implementation process at the Yayasan Kebudayaan Rancage supports SDG objectives, particularly SDG 4 (Quality Education) and SDG 17 (Partnerships for the Goals). Using a qualitative methodology with a single instrumental case study and action research approach, data were collected through observations, interviews, and documentation. Narrative and comparative analysis methods assessed the field conditions to identify challenges and opportunities for improvement. Findings highlight the foundation’s need for a structured budget system to better align with SDG targets, address resource limitations, and increase organizational efficiency. Based on these insights, recommendations include developing a strategic framework that aligns budgets with SDG priorities, creating detailed work plans, and adopting a comprehensive budgeting model. These actions aim to foster a more systematic budgeting process, enhance SDG awareness, and improve stakeholder engagement with sustainable development initiatives